12=-8x-4x

Simple and best practice solution for 12=-8x-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=-8x-4x equation:


Simplifying
12 = -8x + -4x

Combine like terms: -8x + -4x = -12x
12 = -12x

Solving
12 = -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
12 + 12x = -12x + 12x

Combine like terms: -12x + 12x = 0
12 + 12x = 0

Add '-12' to each side of the equation.
12 + -12 + 12x = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 12x = 0 + -12
12x = 0 + -12

Combine like terms: 0 + -12 = -12
12x = -12

Divide each side by '12'.
x = -1

Simplifying
x = -1

See similar equations:

| (x-1)(x-2)(x-3)(x-4)=24 | | 21=1+3k-8k | | 22=1+4p-7 | | 13=5(1+4M)-2 | | 2/7-1/7=3/14 | | 8x-7y+17=0 | | (6y-5p)(y)=(3p)(2p) | | [(2q-3r)-5][(2q-3x+5)]= | | 5(2x-5)=1.5(18x+40) | | 8cos(2x)=5 | | 32-5m= | | 5(v-8)-6=-4(-5v+9)-7 | | (t-4)(4)+(t-1)(4)=(5)(t-1)(t-4) | | sinx=(x^2)/(625pi^2) | | 7=2b-8+1 | | 7.6x-3.4=11.8 | | -5(3n+3)=10 | | (T-9)(T+64)=0 | | 7.5x-1.6=13.4 | | (t+4)(4)+(t+4)(4)=(t-4)(t+4)(5) | | 6.6x-1.3=11.9 | | 4(3z+1)-5(z+8)=3(z+1) | | 1/t-4 | | 21=6-3a-3 | | 8k-4k=0 | | 2+9(x-3)=1-9(x-8) | | 5t*t-8t+112=0 | | n-6-4=-16 | | 6x+24=126 | | -4r-4r=-8 | | 12xy= | | -11-8y=0 |

Equations solver categories